Quantitative Analysis of Phase Separation Using the Lattice Boltzmann Method - Li, Xiaoqi; Fang, Jichao; Ji, Bingyu (Frontiers in Earth Science, 2021)
Phase separation is known in multiphase systems and investigated using Shan-Chen lattice Boltzmann method. The adhesion parameter in SC model leads to the desired fluid-fluid phenomenon. In order to describe such behaviors quantitatively, graphical distributions corresponding to calculated Fourier structure factors are studied. The peak and pre-peak structure factors can correspond each stage over the evolvement of phase separation. Therefore, the structure factor is able to predict complex phase separations accurately.